Utilization of cinnamon Cinnamomum burmannii leaves and shrimp head in the feed on growth performance of catfish Pangasianodon hypopthalmus - Dairun, Suclyadi; Setiawati, Mia; Suprayudi, Muhammad Agus; Utomo, Nur Bambang Priyo (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACTCatfish farming has confronted with the problem of slow growth to reach the fillet size and less tender of fish fillets. This study aimed to investigate the effect of cinnamon leaf flour and shrimp head flour in formulated diets on growth of catfish Pangasianodon hypopthalamus. Catfish with an initial weight of 207.04 ± 2.70 g/fish reared in 12 cages with a dimension of 2×1×1.5 m3 (L×W×H) and its fish density was 15 fishes for 60 days. Fish were fed with following experimental diets: (1) Control; (2) cinnamon leaf (1%) (CL); (3) 45% of protein source from shrimp head (SH); (4) CL+SH mix. The fishes fed twice a day with feeding rate 3.5% of fish biomass. The study found that the use of cinnamon leaf and shrimp head increased the specific growth rate 1.67-1.70%, the feed efficiency 57.55-57.67%, and protein retention 55.61% compared to its control (P<0.05). Triglyceride level, cholesterol, and blood HDL were 416.00-524.05 mg/dL, 139.65-156.68 mg/dL, 73.18-103.70 mg/dL (P>0.05), respectively. HSI value ranged between 0.3-1.9% compared to its control (P<0.05).Keywords: Cinnamomum burmannii, feed, growth, Pangasianodon hypopthalmus, shrimp head. ABSTRAKBudidaya ikan patin dihadapkan pada permasalahan pertumbuhan dan kualitas daging yaitu pertumbuhan yang lambat untuk mencapai ukuran fillet serta tekstur daging kurang kompak. Tujuan penelitian ini adalah untuk menguji pengaruh penggunaan tepung daun kayu manis dan tepung kepala udang dalam pakan terhadap pertumbuhan ikan patin Pangasianodon hypopthalmus. Ikan patin dengan bobot 207,04 ± 2,70 g/ekordipelihara selama 60 hari di hapa sebanyak 12 buah (berukuran 2×1×1,5 m3)dengan padat tebar 15 ekor/jaring. Ikan diberi pakan perlakuan yang terdiri dari: (1) Kontrol; (2) daun kayu manis 1% (DKM); (3) 45% sumber protein dari kepala udang (TKU); dan (4) campuran DKM+TKU. Pemberian pakan sebanyak 2 kali sehari dengan feeding rate 3,5% dari biomassa ikan. Hasil dari penelitian penggunaan daun kayu manis dan kepala udang meningkatkan nilai laju pertumbuhan harian 1,67-1,70%, efisiensi pakan 57,55-57,67% dan retensi protein 55,61% dibanding kontrol (P<0,05). Kadar trigliserida, kolesterol, dan HDL darah berturut-turut adalah 416,00-524,05 mg/dL, 139,65-156,68 mg/dL, 73,18-103,70 mg/dL (P>0,05). Nilai HSI ikan patin berkisar antara 0,3-1,9% dibanding kontrol (P<0,05).Kata kunci: Cinnamomum burmannii, kepala udang, pakan, Pangasianodon hypopthalmus, pertumbuhan.